The Micro Erythrocyte Sedimentation Rate (ESR) Among Chiidren of the Tobacco Plantation Laborers in North Sumatra - Anwar Napitupulu; Rehmamana Sembiring; Chairuddin P. Lubis; S.M. Manoeroen; Helena Siregar (Indonesian Pediatric Society, 1979)
Ninety-four children of the Tobacco Plantation Laborers of the PTP IX, aged between 2 months and 12 years, were investigated on erythrocyte sedimentation rate with the micro ESR method.